1999
DOI: 10.1177/112067219900901s11
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Histological Measures of Retinal Injury in Chronic Ocular Hypertensive Monkeys

Abstract: Components of the multifocal ERG provide a sensitive measure of ganglion cell injury in a monkey model of chronic ocular hypertension. These same measures may have utility in the clinical diagnosis and management of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…For example, in monkey eyes with experimentally induced ocular hypertension, the amplitudes of P1N2 and N2P3 of the first-order kernel as well as the second-order kernel responses were smaller than those in the control eyes by an amount corresponding to the decrease in the number of RGCs caused by the ocular hypertension. 8 Intravitreal injections of TTX in monkeys resulted in the disappearance of the second peak (at about 34 ms) of a two-peaked wave, as reported by Hood and coworkers. 3,4 They suggested that this latter peak probably originated from the RGCs.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For example, in monkey eyes with experimentally induced ocular hypertension, the amplitudes of P1N2 and N2P3 of the first-order kernel as well as the second-order kernel responses were smaller than those in the control eyes by an amount corresponding to the decrease in the number of RGCs caused by the ocular hypertension. 8 Intravitreal injections of TTX in monkeys resulted in the disappearance of the second peak (at about 34 ms) of a two-peaked wave, as reported by Hood and coworkers. 3,4 They suggested that this latter peak probably originated from the RGCs.…”
Section: Discussionsupporting
confidence: 50%
“…The results of experimental studies suggest that mfERGs reflect not only the activity of cells in the outer layers of the retina but also those in the inner retinal layers, such as ganglion cells and amacrine cells. [3][4][5][6][7][8] We recently found a positive wavelet, designated the "swave," in the first-order kernel of human mfERGs. 9 This wave appears on the descending limb of P1 when the base period 10 (bpd) of the stimulus is long.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] In addition, it has also been reported that significant changes are not detected in the amplitude or implicit time of the mfERG after altering the contrast of the pattern stimuli in eyes with POAG. 14 On the other hand, some studies of glaucomatous eyes of experimental animals and humans 2,[5][6][7][15][16][17][18][19] have shown that the waveforms of the first-order kernel of the mfERG reflect the functioning of the cells in the inner layers of the retina, particularly cells in the ganglion cell layer. When the sodium-based action potentials of ganglion cells and amacrine cells were blocked by intravitreal tetrodotoxin in monkey eyes, the amplitude of a small positive wave, which appeared after P1 of the first-order component of the mfERG, was attenuated or disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6,[24][25][26][27][28][29][30][31][32][33] One study reported that the amplitudes of the N1, P1, and N2 of the first-order kernel of the mfERG were smaller and the implicit times were longer in glaucomatous eyes than in normal eyes, but that none of these parameters showed any correlation with the MD as measured by perimetry. 25 On the other hand, another study showed that the MD measurement by perimetry correlated with the amplitude of the P1 and N2 of the first-order kernel responses.…”
Section: Discussionmentioning
confidence: 99%